2017
DOI: 10.1053/j.ajkd.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

KDOQI US Commentary on the 2017 KDIGO Clinical Practice Guideline Update for the Diagnosis, Evaluation, Prevention, and Treatment of Chronic Kidney Disease–Mineral and Bone Disorder (CKD-MBD)

Abstract: Chronic kidney disease-mineral and bone disorder (CKD-MBD) encompasses laboratory and bone abnormalities and vascular calcification and has deleterious effects on clinical outcomes. KDOQI (Kidney Disease Outcomes Quality Initiative), an initiative of the National Kidney Foundation, addressed this issue with the publication of a clinical practice guideline for bone metabolism and disease in CKD in 2003, and 2 years later, a new definition and classification scheme for CKD-MBD was developed following a KDIGO (Ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
249
1
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(270 citation statements)
references
References 57 publications
2
249
1
5
Order By: Relevance
“…It was shown that, in patients with appropriate or high GFR before the first CP administration, eGFR formulae have good accuracy in relation to the reference standard for calculation of the CP dose; CKD-EPI had the best performance (i.e., 0.65), and this has been observed in other nononcology populations with elevated GFR [8]. The formula with the worst performance was CG (i.e., 0.48), which suggests that it is not the best equation to be employed in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was shown that, in patients with appropriate or high GFR before the first CP administration, eGFR formulae have good accuracy in relation to the reference standard for calculation of the CP dose; CKD-EPI had the best performance (i.e., 0.65), and this has been observed in other nononcology populations with elevated GFR [8]. The formula with the worst performance was CG (i.e., 0.48), which suggests that it is not the best equation to be employed in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Creatinuria as a reference standard has some limitations itself, considering that it is the less recommended filtration marker, compared to exogenous markers [8], which, unfortunately, are not performed in Colombia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this recommendation generates some uncertainty and does not provide clear advice on how to treat low BMD in CKD patients, as this patient population was excluded from most RCTs [8]. The language of the updated CKD-MBD guideline is often inconclusive, and all recommendations are at the level of “we suggest” (no level 1 “we recommend”) and the majority have “low” or “very low” levels of evidence.…”
Section: Ckd – Mineral and Bone Disordersmentioning
confidence: 99%